PENDAMPINGAN PENDIDIKAN IMAN ANAK MELALUI PENDIDIKAN AGAMA KRISTEN YANG KREATIF DAN KONTEKSTUAL DI SD NEGERI 36 KOTA SORONG - Natasya Virginia Leuwol; Leidy Damima; Almendo Kereuway; Tia Metanfanuan; Chelsea Gabrella Sani; Leonardus Petra Rumbewas; Zeth Momot; Bentelina Rut Fiay (Yayasan Nusantara Hasana Berdikari, 2025)
This Community Service Program (Pengabdian kepada Masyarakat/PkM) aimed to support children’s faith education through the implementation of creative and contextual Christian Religious Education (CRE) at SD Negeri 36 Kota Sorong. The activity was conducted on Tuesday, December 5, 2024, by lecturers of the Christian Religious Education Program at Universitas Victory Sorong in collaboration with CRE students. The main issue faced by the partner school was the low level of students’ interest and engagement in CRE learning due to the use of conventional and less contextual teaching methods. The program employed an educative, participatory, and contextual approach through interactive Bible storytelling, faith-based educational games, children’s worship songs, simple discussions, and reflective activities adapted to the developmental stages of elementary school students. The results indicated an increase in students’ enthusiasm, active participation, and understanding of Christian faith values such as love, honesty, responsibility, and mutual respect. In addition to benefiting students, the program also contributed to teachers’ insights into innovative CRE teaching methods and provided contextual learning experiences for students as prospective Christian educators. Therefore, creative and contextual CRE-based mentoring proved effective in supporting children’s faith and character development in elementary education.